Virtual reality for prospective and process-related competence modeling—piloting a~participatory approach and investigating user acceptance of the applied VR-tool - Sarah Depenbusch; Niclas Schaper; Jan-Philip Schumacher (Zeitschrift für Arbeitswissenschaft, 2023)
In times of digitalization, it is important to derive competence requirements in relation to future digitalized business processes. Enabling to present these processes in an illustrative and experienceable way, Virtual Reality (VR) may offer special advantages for prospective and process-related competence modeling (PCM) and to include employees as competence modelers. In order to investigate these potential advantages, a~VR-based PCM approach is piloted and compared with a~conventional PCM approach. In order to identify concrete VR-attributes that may be specifically supportive for VR-based PCM, user acceptance of the applied VR-tool has been evaluated. Results show that the realistic visualization and interaction possibilities provided by VR support a~prospective and process-related analysis focus during competence modeling. This way, employees are enabled to identify future competence requirements with regard to single process steps. Comparisons with the conventional PCM approach demonstrate that the prospective and process-related competence models developed in VR provide a~higher level of detail concerning the number of identified competence requirements. In the course of user acceptance evaluation, concrete VR-attributes are derived that are most supportive for participatory PCM (e.g. 3D visualization, perceived immersion). Practical Relevance : VR offers a~space for experiencing new business processes, thus enabling employees to conduct PCM. By integrating employees' expertise, required future competences can be derived validly. On this basis, appropriate measures for effective competence modeling can be implemented in the organization.
Keywords: 650; Digitalization; Virtual Reality; Competence Modeling; Participation; User acceptance; Digitalisierung; Virtual Reality; Kompetenzmodellierung; Partizipation; Nutzerakzeptanz